Mothers' discourse during shared reading of books relating to 'positive' and 'negative' emotions in different genres. (7th July 2021) - Schapira, Rotem; Bergman Deitcher, Deborah; Aram, Dorit
Abstract : Background: The current study provides information about differences in parent–child discourse during shared book reading (SBR) surrounding narrative and didactic book genres about 'positive' (e.g. love, happiness) and 'negative' (e.g. anger and sadness) emotions. Research shows that characteristics of different children's book genres impact discourse during SBR, but narrative and didactic books have not been examined. Children's books often relate to the characters' inner mental and emotional states. Research has not explored parent–child conversations during SBR regarding different types of emotions, yet studies on other discourse contexts reveal that parents discuss 'positive' emotions differently than 'negative' emotions. Methods: Participants were 26 mothers of 5‐ to 6‐year‐olds ( M = 64.30 SD = 6.27). There were 18 boys and 8 girls. Eleven dyads received a narrative and didactic book on 'positive' emotions, and 15 dyads received a narrative and didactic book on 'negative' emotions. Interactions were video‐recorded and analysed. We examined the number of turns, initiations, general utterances and mental–emotional utterances. Results: Primary results revealed that mothers used more general utterances when reading both narrative and didactic books surrounding 'negative' emotions compared with books surrounding 'positive' emotions. Mothers used more mental–emotional utterances with a didactic book on 'negative' emotions compared with a narrative on 'negative' emotions and with a didactic book on 'positive' emotions compared to a narrative on 'positive' emotions. Conclusions: This study highlights the importance of text selection for SBR and how it may impact the discourse. Mothers used didactic books for detailed conversations with their children. The simpler structure of the book may have facilitated the discourse about emotions. Mothers related more to anger and sadness compared with love and happiness. This may indicate that they feel they have to explain and teach their children about 'negative' emotions and how to cope with them, whereas positive emotions may be more implicitly understood.